2019
DOI: 10.1002/chem.201901554
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic‐Assisted Linker Exchange (USALE): A Novel Post‐Synthesis Method for Controlling the Functionality, Porosity, and Morphology of MOFs

Abstract: The introduction of organic ligands into metal–organic frameworks (MOFs) with a specific topology and that cannot be attained by direct synthesis is a big challenge. To meet this challenge, different ligand exchange/incorporation methods have been employed. Here, a new method, called ultrasonic‐assisted linker exchange (USALE), has been developed to overcome the above‐mentioned problems. USALE is a novel method for ligand exchange based on the use of ultrasonic waves. The temperature and pressure caused by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…The post-synthesis ligand exchange method (PSE) exhibits some intrinsic advantages, such as operational simplicity, widespread generality, and thus extensive applications. 110 PSE is typically performed by incubating MOF crystals in a solution containing another pure ligand in the presence of a suitable solvent (DMF or water). Two possible structures of the core–shell and uniformly distributed MOF@MOF heterostructures can be constructed using this technique.…”
Section: Design Principles and Synthetic Approachesmentioning
confidence: 99%
“…The post-synthesis ligand exchange method (PSE) exhibits some intrinsic advantages, such as operational simplicity, widespread generality, and thus extensive applications. 110 PSE is typically performed by incubating MOF crystals in a solution containing another pure ligand in the presence of a suitable solvent (DMF or water). Two possible structures of the core–shell and uniformly distributed MOF@MOF heterostructures can be constructed using this technique.…”
Section: Design Principles and Synthetic Approachesmentioning
confidence: 99%
“…All these structural features can be collectively manifested as inter- or intraframework movements. Significant changes in flexibility and adsorption properties of a given MOF platform have been observed for various metal ions, linkers, or their substituents. These changes can be realized by rational selection of secondary building units, ,, post-assembly linker/metal exchange, , or by covalent post-synthetic modification (CPSM) of linkers. Within the last approach, numerous studies have shown classical nucleophilic substitution , or substitution in a carbonyl group; , however, these reactions typically require chemically stable structures that are resistant to highly corrosive reagents, for example, acyl chlorides or acid anhydrides. Alternatively, to avoid framework degradation, a number of CPSMs have been carried out under mild conditions using Schiff base condensations, , reactions between amines and isocyanates, , or azide–alkyne click reactions. , On the other hand, these reactions suffer from limitations such as low conversion, products prone to hydrolysis, and necessity to use extra additives or catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…[ 19 ] Among N‐heterocyclic ligands, the bispyridyl‐ligand of 1,4‐bis(3‐pyridyl)‐2,3‐diaza‐1,3‐butadiene (3‐bpdb) is a good candidate for construction of coordination architectures. [ 20 ] For example, Arijit Halder and his team used N,N '‐donor ligands to obtain two isostructural two‐dimensional MOFs, namely, {[Zn(3‐bpdb)(suc)] · (H 2 O) 2 }n and {[Zn(3‐bpdb)(fum)(H 2 O) 2 ]}n, which show excellent fluorescence properties (suc = succinate and fum = fumarate). [ 21 ] Divyendu Singh's group reported a 2D CP base on a mixed ligand of 3bpdb and fdc, [Cd(fdc)(3bpdb)(H 2 O)], which has a 2D zig‐zag network structure and excellent fluorescence nature (fdc = 2,5‐furandicarboxylate dianion).…”
Section: Introductionmentioning
confidence: 99%